Komunikasi Dakwah Islam Gus Danang Di Pondok Pesantren Ngawitan Kanjeng Sunan Kalojogo: (Studi kasus di Pondok Pesantren Ngawitan Kanjeng Sunan Kalijogo Walikukun Widodaren Ngawi) - Gozali Rohmat Efrendy (Solidaritas, 2022)
COMMUNICATION OF ISLAMIC DA'WAH GUS DANANG IN PONDOK PESANTREN NGAWITAN KANJENG SUNAN KALIJOGO (Case study at Pondok Pesantren Ngawitan Kanjeng Sunan Kalijogo Walikukun Widodaren Ngawi) ABSTRACT Da'wah communication is a process of interaction of the delivery of religious teachings carried out by someone to others or many people, with the aim of creating an understanding that has an impact on changes in the mindset and behavior of communicant. The purpose of this research is to find out the implementation of Islamic da'wah communication Gus Danang at Pondok Pesantren Ngawitan Kanjeng Sunan Kalijogo. Researchers in analyzing the implementation of Islamic da'wah communication Gus Danang at Pondok Pesantren Ngawitan Kanjeng Sunan Kalijogo using enjang and Aliyudin theory consisting of communication of da'wah bil-lisan and communication dawah bil-qudwah / bil-hal. This type of research is qualitative descriptive research, an informant determination technique using purposive sampling. Data collection techniques use interviews, observations and documentation. The validity of data uses triangulation. Data analysis techniques use interactive analysis. Based on the results of research and discussion, it can be concluded that the implementation of Islamic da'wah communication Gus Danang at Pondok Pesantren Ngawitan Kanjeng Sunan Kalijogo is carried out with several methods of da'wah, namely the bil-lisan (lecture) method and the method of proselytizing bil-hal (action). Through these methods of da'wah, each mad'u is able to absorb the message of da'wah well, although there are still mad'u who have not been able to fully absorb gus Danang's da'wah message. In the course of his da'wah Gus Danang has done as much as possible, namely Gus Danang able to coordinate the santri to obey worship, obey Allah SWT, obey the rules of the hut and the rules of Islam. Keywords: Dawah communication, bil-lisan and bil-qudwah